The Geogenic Radon Potential in the Eastern Part of the Poiana Ruscă Mountains (Southern Carpathians, Romania) - Alexandru Lupulescu; Ștefan Florică; Alexandra Cucoș; Tiberius Dicu; Călin Baciu (Atmosphere)
Detailed soil radon measurements were conducted in the eastern Poiana Ruscă Mountains, motivated by the area’s complex geology, varied topography, and previously reported high indoor radon levels that pose a health risk to local residents. A total of 110 locations were investigated by conducting 330 measurements over a 480 km2 area, using the Radon Monitor-2 (RM-2) and Radon-Jok devices, for assessing the radon activity concentration in soil and soil permeability in correlation with local geological formations. The Neznal method was used to derive the GRP, which was categorized into low (<10), medium (10–35), and high (≥35) risk categories. The arithmetic mean radon concentration was 37.5 kBq/m3, with values ranging from 5.1 to 163 kBq/m3. Soil permeability ranged widely across geological formations, from 6.9 × 10−14 to 2.7 × 10−11 m2. The highest radon concentrations and geogenic radon potential (GRP) values were associated with micaceous schists interlayered with amphibolites and sericitic quartzite schists. The results, comparable to those from previous studies, indicate a medium to high geogenic radon potential in the eastern Poiana Ruscă Mountains, which exposes the inhabitants of Lunca Cernii de Sus and, to a lesser extent, those of Lunca Cernii de Jos to an increased radon risk.